Alpha-actin-2 mutations in Chinese patients with a non-syndromatic thoracic aortic aneurysm. Issue 1 (December 2016) - Ke, Tie; Han, Meng; Zhao, Miao; Wang, Qing; Zhang, Huazhi; Zhao, Yuanyuan; Ruan, Xinlong; Li, Hui; Xu, Chengqi; Sun, Tucheng
Abstract Background Aortic aneurysms and/or dissection (AADs) in the aorta are a leading cause of human morbidity and mortality. To date, data on non-syndromic thoracic AADs (TAADs) have been mainly derived from Caucasians, and the genetic basis of TAADs remains to be elucidated. In this study, we assessed gene mutations in a Chinese population with TAADs. Methods A cohort of 68 non-syndromic familial TAAD Chinese patients was screened for the most common TAAD-causing genes (ACTA2, MYH11, TGFBR1, TGFBR2, andSMAD3 ) using high-resolution melting (HRM) analysis. Thereafter, 142 unrelated non-syndromic sporadic cases were recruited and further analyzed using HRM analysis to estimate the prevalence of disease-causing mutations in these candidate genes. Results Two novelACTA2 mutations (N117I and L348R) were identified in each familial TAAD proband separately, and an additional novelACTA2 mutation (Y168N) was identified in one patient with sporadic TAADs. In contrast, none of the three mutations occurred in 480 control subjects. Also, no other gene mutations were identified in this cohort of Chinese TAAD patients. Conclusions The current study identified three novelACTA2 mutations in Chinese TAAD patients, and these mutations represented the most predominant genes responsible for non-syndromic TAADs. In addition, HRM analysis was shown to be a sensitive and high-throughput method for screening gene mutations.